2006
DOI: 10.1002/eji.200635875
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ negatively regulates Rac/Cdc42 activation in antigen‐stimulated mast cells

Abstract: The Rho GTPases Rac and Cdc42 play a central role in the regulation of secretory and cytoskeletal responses in antigen-stimulated mast cells. In this study, we examine the kinetics and mechanism of Rac and Cdc42 activation in the rat basophilic leukemia RBL-2H3 cells. The activation kinetics of both Rac and Cdc42 show a biphasic profile, consisting of an early transient peak at 1 min and a late sustained activation phase at 20-40 min. The inhibition of phospholipase C (PLC)c causes a twofold increase in Rac an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…As summarized in Fig. 1, antigen stimulates a ∼2.0-fold increase in Cdc42-GTP in RBL-2H3 cells after 1 minute that declined to ∼1.4-fold increase after 3 minutes, consistent with a previous study (El-Sibai and Backer, 2007). Under these conditions, B6A4C1 cells showed somewhat higher basal Cdc42-GTP levels when compared to RBL-2H3 cells (∼15%), and only a very small increase due to antigen stimulation that is not statistically significant.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As summarized in Fig. 1, antigen stimulates a ∼2.0-fold increase in Cdc42-GTP in RBL-2H3 cells after 1 minute that declined to ∼1.4-fold increase after 3 minutes, consistent with a previous study (El-Sibai and Backer, 2007). Under these conditions, B6A4C1 cells showed somewhat higher basal Cdc42-GTP levels when compared to RBL-2H3 cells (∼15%), and only a very small increase due to antigen stimulation that is not statistically significant.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies provided evidence that antigen stimulation of FcεRI in RBL-2H3 mast cells results in activation of the Rho-GTPases Cdc42 and Rac1 (El-Sibai and Backer, 2007) that participate in Ca 2+ mobilization leading to exocytosis of secretory granules (Hong-Geller and Cerione, 2000). Subsequently, we showed that Cdc42 G12V, an activated form of Cdc42, reconstitutes full Ca 2+ mobilization and degranulation in response to antigen in a mutant RBL cell line, designated as B6A4C1, that is defective in these responses (Field et al, 2000; Hong-Geller et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies have demonstrated the activation of the small GTPase Cdc42 in mast cells in response to antigen stimulation (20). Cdc42 is a key regulator of actin dynamics, whose reported effectors in mediating such regulation include N-WASP and the FBP17 homologs Toca1 (21) and CIP4 (22).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of PLCγ1 can increase Ca2 + influx, which is a key regulator for mast cell degranulation [31]. Our study showed no difference in the activation of Syk and PLCγ1 in antigen-stimulated mast cells, explaining that there was no difference in degranulation between SRC-3 -/- and wild-type BMMCs.…”
Section: Discussionmentioning
confidence: 52%